Produção de bioenergia por meio de fermentação alcoólica - Rodrigues, Alessandro Sarmento (Brasil, 2022)
This compendium describes how the process by which the biomass in the figure of a fermented organic compound undergoes addition of an enzyme-containing organic compound that in turn generates an electric capo occurs. This is done through experiments employing the materials described in the future of this record. Fermentation has been employed for a long time in human history for the manufacture of beverages and the baking industry. This is a characteristic process of chemical ceara, which occurs through the absence of oxygen gas (O2), whose fungi and bacteria transform organic matter into other products, including energy. Thus is the way in which these beings use to produce energy and thus for the maintenance and performance of their biological functions. In these experiments, organic materials were used, as previously mentioned, which suffered the action of biological yeast in the figure of Saccharomyces cerevisiae, which is a unicellular eukaryotic microorganism used in the production of bread and also beer, and can, besides being used for the production of fuel alcohol.